PERAN DUKUNGAN KELUARGA DALAM KESEHATAN MENTAL IBU POSTPARTUM - Rahmanindar, Nora; Umriaty (Jurnal Medikes (Media Informasi Kesehatan), 2025)
Women are very vulnerable to depression after childbirth, the postpartum period is the period after birth, from the time the baby is born until the 6th week (40 days), which is the time when the reproductive organs and body systems return to their pre-pregnancy state. In fact, mothers experience an adaptation process during the postpartum period due to changes in their role as mothers. The purpose of this study was to determine the role of family support for postpartum mothers, determine the level of mental health of postpartum mothers, and determine the effect of family support on postpartum mental health in Tegal Regency. The research design was crossectional with a sample of 110 postpartum mothers (0-6 weeks). Data collection used Depression Anxiety and Stress Scale (DASS) assessment questionnaire. Data analysis using Chi-square. The results showed that family support Most postpartum mothers get good family support (79.5%), with only a small proportion feeling that the support provided is sufficient (12.5%) or lacking (6.3%). Mental Health Most postpartum mothers had good mental health, with 76.8% not experiencing stress, 75.9% experiencing anxiety, but the majority not experiencing depression (92.9%). P-value analysis showed statistically significant results for all three mental health variables tested: stress (p value = 0.000), anxiety (p value = 0.000), and depression (p value = 0.004).